Vietnam Tea Industry - An Analysis from Value Chain Approach - Nguyen, Viet Khoi (ĐHKT, 2016)
Over the past two decades, there has been an increasing trend in analyzing international trade from the perspective of Value chains, particularly in agro industry. For many countries, particularly developing countries including Vietnam, agriculture is the backbone of economic development and the main source of income. Together with rice production, Vietnam is also known as one of the most ancient home of tea…